Relasi Antara Pemerintah Daerah Dengan Pedagang Kaki Lima Dalam Upaya Penataan Pedagang Kaki Lima Pantai Padang - Alzyirah, Syahfitri; Sasmita, Siska (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research was motivated by the conflict between Satpol PP and street vendors during the arrangement and control of street vendors on Padang Beach. The Padang City Satpol PP carried out control over street vendors to relocate them to the Culinary Center, but this control was strongly rejected by the street vendors because they were reluctant to leave the beach. This research aims to find out how the relationship between the local government and street vendors is in efforts to organize Padang Beach street vendors. This research uses a qualitative method with a descriptive approach. The data collection techniques used were interviews and documentation. Informants in this research included the Padang City Tourism Office, Padang City Satpol PP and Padang Beach street vendors. The results of the research show that the relationship between the local government and street vendors in efforts to organize Padang Beach street vendors is not running harmoniously. Judging from the Relationship Management Theory according to Hon and Gruning (1999), only two dimensions of the four dimensions of relationship management are working well, namely trust and commitment, but this only happens at the beginning of control. Meanwhile, the dimensions of control over relationships and satisfaction do not work well.